Experiments probing clustering effects in explosive nucleosynthesis - Bardayan, D. W. (Frontiers in Physics, 2023)
Nuclear clustering affects the nucleosynthesis occurring in a number of astrophysical environments. Highly-clusterized nuclear states typically occur near particle thresholds and therefore can produce dramatic impacts on the nuclear reaction rates. This is especially true for astrophysical explosions that are driven by the consumption of helium as fuel. Such burning can occur in X-ray bursts, supernovae type Ia, and core-collapse supernovae for instance. This article will focus on the explosive astrophysical events in which nuclear clustering is most important, will discuss the types of information and tools necessary to estimate the astrophysical reaction rates, and will discuss example experiments at Notre Dame and other facilities that have or will be performed to measure the critical nuclear data needed for such estimates.